2020 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2020
DOI: 10.1109/tale48869.2020.9368493
|View full text |Cite
|
Sign up to set email alerts
|

Delivering an Effective Balance of Soft and Technical Skills within Project-Based Engineering Courses

Abstract: knowledge that is largely theoretical, and industry needs to invest considerably to close off the knowledge gap between principles as taught and codified knowledge as used in industry" [2]. Unfortunately, this is not an isolated assessment, with multiple studies showing that engineering graduates do not meet industry [3][4][5][6] or program accreditation expectations [7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Although these results indicate students are performing above average at both Year 2 and 4 (and this is similar to the conclusions of Konings and Legg (2020) for a Year 3 project) the students often modify the scope of the project to meet the constrained time of the semester or double semester project as well providing only very high level detail Gantt charts and sometimes a Kanban system of task management. The responses by the students confirm that students are modifying the project scope but were able to mainly maintain processes throughout the project.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Although these results indicate students are performing above average at both Year 2 and 4 (and this is similar to the conclusions of Konings and Legg (2020) for a Year 3 project) the students often modify the scope of the project to meet the constrained time of the semester or double semester project as well providing only very high level detail Gantt charts and sometimes a Kanban system of task management. The responses by the students confirm that students are modifying the project scope but were able to mainly maintain processes throughout the project.…”
Section: Resultssupporting
confidence: 58%
“…It has been observed that students have difficulty in planning and monitoring team projects, particularly double-semester projects, as the team may not realise that they have fallen behind (Konings & Legg, 2020). To some degree this is avoided through regular meetings with supervisory staff but where increasing autonomy is expected, there is less contact with staff, and the workloads of other courses are high, especially in the final year, it is easy for student teams to end up significantly behind planned objectives (Konings & Legg, 2020). Lawanto, Cromwell, and Febrian (2016) presented the components of project management used by students for self-regulation of the Capstone projects broken down into team management, time management and resources management.…”
Section: Introductionmentioning
confidence: 99%